2015
DOI: 10.1890/es15-00065.1
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting sapling bark allocation of five southeastern USA hardwood tree species in a fire prone ecosystem

Abstract: Abstract. Fire affects numerous aspects of plant growth and anatomy, particularly in those species adapted to persist in fire-prone environments. A key aspect of tree survival is rapid accumulation of protective bark within fire return intervals. We compared bark accumulation in five co-occurring hardwood species within a longleaf pine (Pinus palustris) ecosystem in the mountains of northeastern Alabama, USA. Sampled species included blackjack oak (Quercus marilandica), sand hickory (Carya pallida), common per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 61 publications
(94 reference statements)
1
36
1
Order By: Relevance
“…The "super-generalist" red maple (Abrams 1998) is often the most intense competitor to oakhickory regeneration in many areas of the Central Hardwoods, and sprouts vigorously following a harvest or a single fire (Albrecht and McCarthy 2006, Iverson et al 2008, Schuler et al 2013, Thomas-Van Gundy et al 2015. However, we found that subsequent fires continually reduced abundance of red maple in the large seedling and sapling layers, and by Y13, most of the larger red maple stems had been eliminated; the thin bark of red maple makes it especially sensitive to heat damage and its sprouting capacity was reduced with multiple fires (Hare 1965, Harmon 1984, Hammond et al 2015. Similar results on fire impacts on red maple were reported by Arthur et al (2015) in Kentucky.…”
Section: Dynamics Of Competing Vegetationmentioning
confidence: 65%
See 1 more Smart Citation
“…The "super-generalist" red maple (Abrams 1998) is often the most intense competitor to oakhickory regeneration in many areas of the Central Hardwoods, and sprouts vigorously following a harvest or a single fire (Albrecht and McCarthy 2006, Iverson et al 2008, Schuler et al 2013, Thomas-Van Gundy et al 2015. However, we found that subsequent fires continually reduced abundance of red maple in the large seedling and sapling layers, and by Y13, most of the larger red maple stems had been eliminated; the thin bark of red maple makes it especially sensitive to heat damage and its sprouting capacity was reduced with multiple fires (Hare 1965, Harmon 1984, Hammond et al 2015. Similar results on fire impacts on red maple were reported by Arthur et al (2015) in Kentucky.…”
Section: Dynamics Of Competing Vegetationmentioning
confidence: 65%
“…However, we found that subsequent fires continually reduced abundance of red maple in the large seedling and sapling layers, and by Y13, most of the larger red maple stems had been eliminated; the thin bark of red maple makes it especially sensitive to heat damage and its sprouting capacity was reduced with multiple fires (Hare , Harmon , Hammond et al. ). Similar results on fire impacts on red maple were reported by Arthur et al.…”
Section: Discussionmentioning
confidence: 95%
“…Although allometric equations that predict bark thickness from DBH exist for a portion of the upland forest tree species examined (e.g. Harmon 1984;Hengst and Dawson 1994), in eastern forests, where the historic fire regime was dominated by frequent low severity fire (Lafon et al 2017), it is possible that bark thickness at the base of the bole rather than at breast height is more of a factor influencing fire-related mortality for the species examined (Graves et al 2014;Hammond et al 2015). In regard to the limitations of the data, for Acer rubrum, Cornus florida, Oxydendrum arboreum, Nyssa sylvatica and Sassafras albidum, there is a limited number of trees in the larger size classes (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Fires impact forests at different scales, depending upon their intensity, duration, return interval (Brooks, Richardson, & Grace, ; Certini, ), and on the resilience of the affected ecosystem (Díaz‐Delgado, Lloret, Pons, & Terradas, ; Larson, Belote, Cansler, Parks, & Dietz, ). Although there are forests in which fire is part of their natural dynamic (Appiah, ; Larson et al, ), in forests that are adapted to a low frequency of fires, these events can cause variable mortality among species that are lacking the usual adaptive traits to fire (Hammond, Varner, Kush, & Fan, ; Nasi et al, ) and may irreversibly change floristic composition (Cochrane & Schulze, ; Woods, ). These effects are exacerbated due to the clear increase in human‐caused fires (Syphard, Radeloff, Hawbaker, & Stewart, ; Wittenberg & Malkinson, ).…”
Section: Introductionmentioning
confidence: 99%